Sistem Pendukung Keputusan Penilaian Kinerja Ormawa di Politeknik Negeri Bengkalis dengan Metode Multifactor Evaluation Process (MFEP) - Nurul Liyana Ulfa; Ryci Rahmatil Fiska (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
The performance evaluation of student organizations (Ormawa) at Politeknik Negeri Bengkalis is an essential part of the end-of-term management assessment, serving as a form of accountability and a basis for future development. The manual process used so far often takes considerable time and is prone to errors. To address this issue, a web-based decision support system was developed using the Multi-Factor Evaluation Process (MFEP) method, which applies a weighting system in the decision-making process. The system was developed using the Rapid Application Development (RAD) approach, enabling a fast and efficient development process through a linear and sequential methodology. The implementation of the MFEP method in the system achieved an accuracy rate of 88.88%, based on a comparison between field data and system processing results.